Simulation of Whirlpool Galaxy and its Companion - Rasheed, Mariwan A. (Sulaimani Journal for Pure and Applied Sciences, 2009)
In the present work the Whirlpool galaxy and its companion are simulated using Intergalactic Gravitational Motion Simulator IGMS code. N-body method is depended in simulating 480 particles. From the simulation, it was found that the spiral shape and the arm of the whirlpool galaxy were constructed by interaction with its companion. In addition, the interaction caused the tidal bridge between the two galaxies and distorted the shape of the whirlpool galaxy to a perfect spiral galaxy. It was also found that the two galaxies started the interaction in the nearer position for hundreds million years and after that the two galaxies separate from each other.The results indicated that the simulation image matches with that observed by telescopes.
Keywords: simulation in astronomy; simulation of Whirlpool galaxy; whirlpool galaxy